Modulatory Effect of Aerobic Physical Activity on Synaptic Ultrastructure in the Old Mouse Hippocampus - Fattoretti, Patrizia; Malatesta, Manuela; Cisterna, Barbara; Milanese, Chiara; Zancanaro, Carlo (Frontiers in Aging Neuroscience, 2018)
Aerobic physical exercise (APE) leads to improved brain functions. To better understand the beneficial effect of APE on the aging brain, a morphometric study was carried out of changes in hippocampal synapses of old (>27mo) Balb-c mice undergoing treadmill training (OTT) for four weeks in comparison with old sedentary (OS), middle-aged sedentary (MAS), and middle-aged treadmill training (MATT) mice. The inner molecular layer of the hippocampal dentate gyrus (IMLDG) and the molecular stratum of Ammon’s horn1 neurons (SMCA1) were investigated. The number of synapses per cubic micron of tissue (numeric density, Nv), overall synaptic area per cubic micron of tissue (surface density, Sv), average area of synaptic contact zones (S), and frequency (%) of perforated synapses (PS) were measured in electron micrographs of ethanol-phosphotungstic acid stained tissue. Data were analyzed with ANOVA. In IMLDG, an effect of age was found for Nv and Sv, but not S and %PS. Similar results were found for exercise and the interaction of age and exercise. In post-hoc analysis Nv was higher (60.6% to 75.1%; p<0.001) in MATT vs. MAS, OS, and OTT. Sv was higher (32.3% to 54.6%; p<0.001) in MATT vs. MAS, OS, and OTT. In SMCA1, age affected Nv, Sv, and %PS, but not S. The effect of exercise was significant for Sv only. The interaction of age and exercise was significant for Nv, Sv, and %PS. In post-hoc analysis Nv was lower in OS vs. MAS, MATT, and OTT (-26.1% to -32.1%; p<0.038). MAS and OTT were similar. Sv was lower in OS vs. MAS, MATT, and OTT (-23.4 to -30.3%, p<0.004). MAS and OTT were similar. PS frequency was higher in OS vs. MAS, MATT, and OTT (48.3% to +96.6%, p<0.023). APE positively modulated synaptic structural dynamics in the aging hippocampus, possibly in a region-specific way. The APE-associated reduction in PS frequency in SMCA1 of old mice suggests that an increasing complement of PS is a compensatory phenomenon to maintain synaptic efficacy. In conclusion, the modulation of synaptic plasticity by APE gives quantitative support to the concept that APE protects from neurodegeneration and improves learning and memory in aging.